Impact of MSME Effectiveness and Governance on MSME Performance ( Case Study: Palopo Msme Post Covid 19) - Samsuri Samsuri; Muh. Yusuf Qamaruddin; M. Risal (Jurnal Mantik, 2021)
This corona virus disease or Covid-19 has hit and stomped the joints of the economic and social life of the community. This pandemic has infected most of the countries in the world. Indonesia is no exception as one of the countries that feel the impact. In Indonesia, where the percentage of Micro, Small and Medium Enterprises (MSME) is quite high, it is hoped that there will be a strategic policy towards the MSME sector which has an important role in building the nation's economy. The purpose of this research is to find out the extent of the impact of MSME Policy and Governance during and after Covid-19 on MSME performance in Palopo City. The results showed that the effectiveness and governance of MSME had an effect on the performance of MSME either partially or simultaneously.